Habitualisasi Gerakan Pilah Sampah Dari Rumah pada Warga Desa Kertayasa Kecamatan Sindang Agung Kabupaten Kuningan - Aziz, Rohmanur; Dewi, Ratna (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2025)
ABSTRACT This community service program aims to strengthen the habitualization of household waste sorting as an effort to build ecological behavior among residents of Kertayasa Village, Sindangagung District, Kuningan Regency. The method used includes social mapping of 2,502 respondents through in-depth interviews, and descriptive qualitative analysis. The results show that community knowledge and awareness of waste management are high, but the practice of waste sorting remains situational. The process of habit formation occurs through continuous education, exemplary leadership, institutional support, and the integration of Islamic values of cleanliness (thaharah). This activity confirms that the success of community-based 3R waste management requires sustainable social habit formation through the integration of religious values, community participation, and local institutional reinforcement. Keywords : Habitualization, 3R Waste Management, Community Empowerment, Kertayasa Village